The Role of Lecturer's Pedagogical and Entrepreneurial Competence in Shaping Student Entrepreneurial Engagement and Intention: A Proposed Framework - Wijayati, Ary; Heryatno, Roni; Ali, Hapzi; Daniel, Hans; Prakosa, Gatot Hendro (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This paper proposes a comprehensive framework examining how lecturer competencies influence student entrepreneurial outcomes in higher education. Drawing from social cognitive theory and experiential learning perspectives, we develop five hypotheses exploring the relationships between lecturer's pedagogical competence, lecturer's entrepreneurial competence, student entrepreneurial engagement, and student entrepreneurial intention. The framework suggests that both pedagogical and entrepreneurial competencies of lecturers play crucial roles in fostering student engagement and intention toward entrepreneurship. Additionally, student engagement serves as a critical mediating factor in developing entrepreneurial intentions. This conceptual paper contributes to entrepreneurship education literature by distinguishing between different types of lecturer competencies and their unique impacts on student outcomes.